2018
DOI: 10.3390/su10124801
|View full text |Cite
|
Sign up to set email alerts
|

Food Purchasing Characteristics and Perceptions of Neighborhood Food Environment of South Africans Living in Low-, Middle- and High-Socioeconomic Neighborhoods

Abstract: Using intercept surveys, we explored demographic and socioeconomic factors associated with food purchasing characteristics of supermarket shoppers and the perceptions of their neighborhood food environment in urban Cape Town. Shoppers (N = 422) aged ≥18 years, categorized by their residential socioeconomic areas (SEAs), participated in a survey after shopping in supermarkets located in different SEAs. A subpopulation, out-shoppers (persons shopping outside their residential SEA), and in-shoppers (persons resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…In addition, supermarkets in urban poor areas tend to offer less variety of healthy products (i.e. fresh produce) and oftentimes products of lower quality [ 71 ]. Such fragmented market can lead to the establishment of informal arrangements, especially in low- and middle-income countries, such as street traders and house shops that are more likely to be unstable and deregulated [ 43 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, supermarkets in urban poor areas tend to offer less variety of healthy products (i.e. fresh produce) and oftentimes products of lower quality [ 71 ]. Such fragmented market can lead to the establishment of informal arrangements, especially in low- and middle-income countries, such as street traders and house shops that are more likely to be unstable and deregulated [ 43 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is assumed that along with availability and accessibility, nutrition education might have also influenced AI households, to consume the fish species produced in their ponds. This kind of fish consumption behavior indicates the importance of the food environment and the necessity of health promotion activities, to promote intake of specific target foods [37,38]. In Bangladesh, the most cultivated fish species are: carp species, tilapia, pangasius, and in some cases mola carplet; due to the availability of proven production technologies and these species are more resilient to the environment [21,22,39].…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic characteristics of interest include household income levels, education, gender, and age of the household head, household size and structure, ethnicity, religion, car ownership, among others. Previous research showed that these characteristics can influence the decision of which retailers to use [13,15,[22][23][24]32]. The use of different retailers is measured through a set of dummy variables capturing whether or not the household purchased any food from a particular type of retailer during the 7-day recall period.…”
Section: Measurement Of Key Variablesmentioning
confidence: 99%
“…However, at the same time consumer preferences and demand may also be shaped by changing food environments [10][11][12]. For example, a shift from traditional markets to modern supermarkets and hypermarkets has effects on the types of food offered, as well as on food variety, food prices, and shopping atmosphere, all of which may influence consumer choices [3,[13][14][15]. Understanding the links between changing food environments and food consumption patterns is important to promote food security and healthy diets.…”
Section: Introductionmentioning
confidence: 99%